2020
DOI: 10.1038/s41598-020-73433-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of knee flexor submaximal isometric contraction until exhaustion on semitendinosus and biceps femoris long head shear modulus in healthy individuals

Abstract: This study examined whether a knee flexor isometric contraction at 20% of maximal voluntary isometric contraction until exhaustion would alter the biceps femoris long head (BFlh) and semitendinosus (ST) active stiffness, assessed using ultrasound-based shear wave elastography. Twelve healthy individuals participated in 2 sessions separated by 7 days. Time to exhaustion was similar in both sessions (day 1: 443.8 ± 192.5 s; day 2: 474.6 ± 131.7 s; p = 0.323). At the start of the fatigue task, the ST showed great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 47 publications
6
35
0
Order By: Relevance
“…These changes are opposite to those seen in ECC, despite similar reductions in MVT, suggesting that fatigue affects hamstrings load bearing differently, depending on contraction type. The greater relative load borne by BFlh during ISO is consistent with previous shear wave elastography studies 21,22 . In those studies, BFlh active stiffness remained constant during a sustained isometric contraction at 20%MVC, while that of ST was reduced, thereby increasing the BFlh/ST ratio towards the end of the task 21,22 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These changes are opposite to those seen in ECC, despite similar reductions in MVT, suggesting that fatigue affects hamstrings load bearing differently, depending on contraction type. The greater relative load borne by BFlh during ISO is consistent with previous shear wave elastography studies 21,22 . In those studies, BFlh active stiffness remained constant during a sustained isometric contraction at 20%MVC, while that of ST was reduced, thereby increasing the BFlh/ST ratio towards the end of the task 21,22 .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, two recent SWE studies reported a decrease in ST shear elastic modulus (i.e. index of tissue stiffness, directly related to muscle force), but no change in BFlh during a low-intensity sustained isometric contraction in healthy individuals 21 and previously injured elite footballers 22 , suggesting greater fatigue in ST. These ndings support the concept of selective fatigue within the hamstrings; however, they point to different muscle being affected.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The present results provide important methodological insights regarding the use of SWE to examine the localized muscle stiffness during contraction. Previous studies have only assessed stiffness at a single muscle region [ 8 , 9 , 10 , 23 ], assuming a homogeneous distribution along the muscle’s length. Our results show that such an assumption is flawed and that regionalized differences should be taken into consideration, particularly during low intensity contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of ultrasound-based shear wave elastography (SWE), several studies have recently investigated the stiffness of different muscles in vivo during contraction (i.e., active stiffness) through estimates of localized shear modulus [ 8 , 9 , 10 ]. Although the validity of these measurements has not been fully explored, the aforementioned studies have only assessed the muscle stiffness at a single region, assuming stiffness homogeneity throughout the muscle length.…”
Section: Introductionmentioning
confidence: 99%